2004
DOI: 10.1139/t04-039
|View full text |Cite
|
Sign up to set email alerts
|

Numerical model verification and calibration of George Massey Tunnel using centrifuge models

Abstract: Dynamic soil–structure interaction analyses were carried out for the seismic retrofit design of the immersed George Massey Tunnel, both to predict and study soil liquefaction and related tunnel movements and to design ground improvement. The proposed ground improvement included ground densification using vibroreplacement stone columns along both sides of the tunnel and seismic gravel drains adjacent to the outer edge of the densified zones. The den sification and drainage were proposed to locally mitigate soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…The possibility of uplift of underground structures in a major earthquake was supported by several numerical and experimental analyses. Numerical analyses carried out by Yang et al [5] on the George Massey Tunnel and Sun et al [6] on the BART tunnel showed significant floatation. However, these analyses were carried out for very specific cases and site conditions.…”
Section: Introductionmentioning
confidence: 92%
“…The possibility of uplift of underground structures in a major earthquake was supported by several numerical and experimental analyses. Numerical analyses carried out by Yang et al [5] on the George Massey Tunnel and Sun et al [6] on the BART tunnel showed significant floatation. However, these analyses were carried out for very specific cases and site conditions.…”
Section: Introductionmentioning
confidence: 92%
“…There was a conflict between the dynamic and permeability time scales. To solve the problem, methyl cellulose fluid was introduced to reduce the permeability of soil [26]. Methyl cellulose fluid was introduced at a rate of 0.1 L/h into the model foundation when cooling down, which was slow enough to avoid the sand boiling phenomenon.…”
Section: Model Preparationmentioning
confidence: 99%
“…They concluded that the placement of coarse backfill above underground pipes can reduce their uplift displacements caused by soil liquefaction. Yang et al (2004) performed centrifuge and numerical analyses for the case of the George Massey Tunnel in British Columbia, and proposed applying densification or gravel drainage columns on either side of the box tunnel. Both methods produced a reduction in uplift displacement of the structure.…”
Section: Stone Column/coarse Backfillmentioning
confidence: 99%